Perbaikan tanah melalui mediasi hayati [Bio-mediated soil improvement] - Didiek H GOENADI (Menara Perkebunan, 2017)
Soil properties unsuitable to support physical requirements oftenly become problems in utilizing it for agricultural as well as construction purposes.  Most common practice to overcome the problems is by applying chemical agent which are not only expensive but also un-enviromentally friendly.  Therefore, it is imperative to seek a new, sustainable, and innovative technology to improve mechanical soil properties.  Many researches gave opportunity to utilize microbes for this idea.  However, the direct application of this technology faces some handicaps in the field, i.e. soil and pore fluid interaction, bio-augmentation verses bio-stimulation of microbial community, controlled distribution of bio-mediated calcite precipitation, and permanence cementation.  This article aims at providing a general overview regarding technological development to improve soil mechanical properties suitable for construction by applying microbes.